Pengaruh Kualitas Layanan Terhadap Loyalitas Melalui Kepuasan Pelanggan di Pizza Hut Merr Surabaya - Rizka Novianty Haninda; Eko Winarni; Jamianto (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
The growing number of restaurants has resulted in intense competition to attract restaurants. Pizza Hut MERR Surabaya is one of the big restaurants in Surabaya. It is located on The Road Dr. Ir. H. Soekarno Kel. Kedung Baruk Kec. Rungkut Surabaya. Pizza Hut MERR Surabaya has many visitors in addition to having a large building area, this restaurant also has complete facilities. Pizza Hut MERR Surabaya is surrounded by other magnificent buildings such as fast food restaurants, star hotels, companies, large malls, apartments and elite housing. The location affects consumers who come to Pizza Hut MERR Surabaya. Consumers are dominated by the upper middle class with a sufficient economy. This study aims to analyze the effect of quality of service positively on customer loyalty at Pizza Hut MERR Surabaya; to positively analyze the effect of quality of service on customer satisfaction at Pizza Hut MERR Surabaya; to positively analyze the effect of satisfaction on customer loyalty at Pizza Hut MERR Surabaya; and to analyze the effect of quality of service positively on loyalty through customer satisfaction at Pizza Hut MERR Surabaya. The type of research used in this research uses quantitative methods and Path Analysis Techniques. The sample population is 105 customers at Pizza Hut MERR Surabaya. The analytical technique used in this research is Path Analysis. The results of the analysis can be concluded that the quality of service positively affects customer loyalty at Pizza Hut MERR Surabaya; The quality of service positively affects customer satisfaction at Pizza Hut MERR Surabaya; Satisfaction positively affects customer loyalty at Pizza Hut MERR Surabaya; and Quality of service positively affects loyalty through customer satisfaction at Pizza Hut MERR Surabaya but customer satisfaction is not an intervening variable.